2017 Staff Guidance Note on the Fund's Engagement with Small Developing States. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2018)
This guidance note highlights the unique economic characteristics and constraints facing small developing states. It provides operational guidance on Fund engagement with such countries, including on how small state characteristics might shape Fund surveillance and financial support, program design, capacity building activities, and collaboration with other institutions and donors. The note updates the previous version that was published in May 2014. It incorporates modifications resulting from Board papers and related Executive Board discussions that have taken place since the March 2013 Board papers on small states, which provided the foundations of the original guidance note. Based on these inputs, five key thematic areas (G.R.O.W.TH.) have been identified as central to the policy dialogue: -- Growth and job creation. With small states experiencing relatively weak growth since the 1990s, Fund staff working on small states should ensure an explicit focus on growth in both surveillance and program-related work. -- Resilience to shocks. Small states experience higher macroeconomic volatility and more frequent natural disasters. Staff should be ready to advise on how to tailor macroeconomic policies to provide greater resilience to shocks and climate change. -- Overall competitiveness. Options to improve relative prices may include exchange rate adjustment (where possible) or measures supportive of internal devaluation (if not), and efforts to improve the business climate, including through regional initiatives. -- Workable fiscal and debt sustainability options. With many small states having very high debt burdens, reducing debt to manageable levels requires sustained fiscal consolidation with supporting policies and structural reforms. In cases where the amount of adjustment needed to restore debt sustainability is not feasible or adequate financing is not available, debt restructuring may be needed. -- Thin financial sectors. Developing deeper and more competitive, yet sound, financial sectors contributes to macroeconomic stability and enhances the effectiveness of policy interventions while strengthening competitiveness by improving business access to financial services.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet